1977
DOI: 10.1002/jsfa.2740280502
|View full text |Cite
|
Sign up to set email alerts
|

Castorbean allergens in tissues of catfish reared on a diet containing castorbean pomace

Abstract: Channel catfish were reared to pan size on an experimental diet containing 50% castorbean pomace that had been detoxified by cooking during oil removal. This pomace was still highly allergenic due to the presence of heat stable antigenic proteins. Muscle tissue from catfish currently being fed castor pomace contained clinically significant amounts of active castorbean allergens, but muscle from fish that had been taken off the pomace a week earlier did not. Fish reared on allergenic castorbean pomace should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Jenkins (13) found that autoclaving castor seeds at 15 psi (presumably at 121 °C) for 1 h or boiling solutions of ricin for 2 min fully detoxified ricin as measured in a rat feeding study. Layton (19) reported that catfish fed castor bean meal obtained by steam extraction of the castor seeds (conditions not specified) did not exhibit signs of toxicity while Gardner et al (20) found that heating flaked castor bean at 100-102 °C for 12-15 min was sufficient to detoxify the toxic components of castor beans. Okorie and Anugwa (14) found that steaming castor beans at 80 °C for up to 40 min did not destroy ricin, while dry heating the beans at 140 °C for 20-30 min was sufficient to inactivate the toxin.…”
Section: Resultsmentioning
confidence: 99%
“…Jenkins (13) found that autoclaving castor seeds at 15 psi (presumably at 121 °C) for 1 h or boiling solutions of ricin for 2 min fully detoxified ricin as measured in a rat feeding study. Layton (19) reported that catfish fed castor bean meal obtained by steam extraction of the castor seeds (conditions not specified) did not exhibit signs of toxicity while Gardner et al (20) found that heating flaked castor bean at 100-102 °C for 12-15 min was sufficient to detoxify the toxic components of castor beans. Okorie and Anugwa (14) found that steaming castor beans at 80 °C for up to 40 min did not destroy ricin, while dry heating the beans at 140 °C for 20-30 min was sufficient to inactivate the toxin.…”
Section: Resultsmentioning
confidence: 99%